The Effect Of Boiled Sail Leaf Water On Blood Pressure In Hypertension Patients - Rini, Rini; Sylvia, Ester Inung; Kusnaningsih, Aida; Datak, Gad (Journal of Midwifery and Nursing, 2024)
Hypertension is a major health problem that can cause complications from various diseases such as heart disease, stroke, kidney failure and other diseases. One effort to lower blood pressure is with bay leaf boiled water therapy. Bay leaves contain flavonoids which function to relax arterial muscles so they can reduce high blood pressure in hypertensive patients. The aim of the research was to determine the effect of bay leaf boiled water therapy on blood pressure in hypertensive patients. The research design used a quasi-experiment with a one group pre-post test design approach, the sample size was 39 people using a purposive sampling technique. The patient drank water boiled with bay leaves ½ glass in the morning and ½ glass before eating for 2 weeks. Blood pressure was measured before and after drinking boiled bay leaves. The results of the research before therapy were carried out, the average systolic blood pressure was 160.67 mmHg and diastolic 93.1 mmHg, after therapy with bay leaf boiled water the average systolic blood pressure was 147.74 mmHg and diastolic 81.72 mmHg. The results of the analysis showed that bay leaf boiled water therapy had an effect on reducing blood pressure in hypertensive patients at the Menteng Community Health Centers, Palangka Ra (p=0.00)